Integrasi Model Talking Stick dan Trade A Problem melalui Media Interaktif untuk Meningkatkan Keterampilan Belajar Matematika Siswa Kelas IV SD Negeri 1 Ngronggah - Devita Kusumaningrum; Aqidatul Munfariqoh; Ahmad Teguh Purnawanto (Paedagogie, 2026)
This study aims to describe the implementation of the integration of the Talking Stick and Trade a Problem learning models through interactive media, to explain the process of their application, and to determine the improvement of mathematics learning skills of fourth-grade students at SD Negeri 1 Ngronggah. This research employed a Classroom Action Research (CAR) approach using a spiral model consisting of planning, action, observation, and reflection stages conducted in two cycles. The research subjects were 15 students. Data were collected through observation, interviews, questionnaires, documentation, and tests. Data analysis used descriptive qualitative methods to describe the learning process and descriptive quantitative methods to measure the improvement of students’ learning outcomes. The results showed a significant improvement in students’ mathematics learning skills in each cycle, indicated by an increase in the average score from 67.3 in the pre-cycle to 72.5 in cycle I and 81.2 in cycle II, as well as an increase in learning mastery from 6% to 53% and then to 86%. In addition, students became more active, confident, and collaborative during the learning process. In conclusion, the integration of the Talking Stick and Trade a Problem models through interactive media is effective in improving students’ mathematics learning skills in cognitive, affective, and social aspects, and in creating a more interactive and meaningful learning environment.